SYSTEMATIC REVIEW METODE INTERVENSI PENGETAHUAN MASYARAKAT DALAM PENGENDALIAN KASUS LEPTOSPIROSIS DI WILAYAH KOTA SEMARANG - Sri Wahyu Ningsih; M. Sakundarno Adi; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2019)
Knowledge interventions in the Semarang were carried out by many health institutions but from the results of these intervention activities, there was no systematic review of the methods of intervention of community knowledge in the control of leptospirosis cases. This review aims to identify articles about the intervention method of knowledge and effectiveness in increasing public knowledge in controlling leptospirosis in the Semarang City. Searching for research articles in several databases using certain keywords in the period 2010-2018 and gray literature. Search results obtained 47 articles and only 3 articles that met the inclusion criteria. Researchers assessed articles using the Critical Appraisal Skills Program (CASP) for A Systematic Review. The results of the Systematic Review show that the intervention of community knowledge varies in terms of methods. The knowledge intervention method consists of poster methods, lectures, lectures-simulations and lectures-demonstrations. Statistical analysis shows that all of these methods can improve people's knowledge about Leptospirosis and its control significantly. The results of changes in knowledge scores with the lecture method were 26.53, the poster method was 36.54, the lecture-simulation method was 46.11 and the lecture-demonstration method was 44.27 from the initial knowledge. The highest change in scores for public knowledge about leptospirosis is lecture-simulation method. Knowledge intervention methods that can be recommended to be applied by extension workers and leptospirosis control program holders are lecture-simulation methods because they have the advantage of being able to increase public knowledge and provide the experience needed by the community to prevent and control leptospirosis.